2020
DOI: 10.4012/dmj.2019-027
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive bonding of alumina air-abraded Ag-Pd-Cu-Au alloy with 10-methacryloyloxydecyl dihydrogen phosphate

Abstract: The aim of this paper is to study changes in the Ag-Pd-Cu-Au alloy surfaces by alumina air-abrasion process and effect of those changes on the adhesive bonding characteristic. Surface roughness, surface composition and chemical state of the alumina airabraded alloys were analyzed by a confocal laser scanning microscope, an energy dispersive X-ray spectroscopy and an X-ray photoelectron spectroscopy. The results showed that the alumina air-abrasion changed the alloy surface by mechanical roughening, alumina rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…An abrader (Jet Blast II, J. Morita Corp., Suita, Japan) was used for 20 sec at 0.6 MPa of air pressure; the distance from the nozzle to the surface of the specimens was 10 mm. The processing conditions were based on previous reports [17][18][19]. Superfluous alumina on the surface of the specimens was subsequently removed with acetone.…”
Section: Specimen Preparation For Shear Bond-strength Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…An abrader (Jet Blast II, J. Morita Corp., Suita, Japan) was used for 20 sec at 0.6 MPa of air pressure; the distance from the nozzle to the surface of the specimens was 10 mm. The processing conditions were based on previous reports [17][18][19]. Superfluous alumina on the surface of the specimens was subsequently removed with acetone.…”
Section: Specimen Preparation For Shear Bond-strength Testsmentioning
confidence: 99%
“…The specimens of each metal (Ti and IV) were divided into four sets (n = 30), and each of the four primers (MC, MCA, AP, or VP) was applied to each set. The method of preparing the specimens for the groups before and after thermocycling, experimental conditions for the shear bond strength test with thermocycling, and classification of failure modes in the specimen bond region were the same as in previous studies [14,15,18,19]. The sample size was calculated using a specific application (G*Power 3.1.9.2, Heinrich Heine University, Dusseldorf, Germany) [20].…”
Section: Specimen Preparation For Shear Bond-strength Testsmentioning
confidence: 99%
“…The ROC tribochemical system introduced the silica-coating method with alumina-abrasion, followed by impact silicacoated alumina onto adherend materials. The types of alloys and alumina particle sizes influenced the number of particles retained on the abraded surface 31,32) , which were suspected to affect the Rz and RSm values. With respect to the surface characteristics, the comparison of Rz values showed that the No.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, alumina air-abrasion of a Ag–Pd–Cu–Au alloy both mechanically roughens and chemically alters the surface, thereby increasing the surface area [ 12 , 13 ]. Two chemical alterations (the remaining alumina particle component and the oxidation of copper ions on the alloy surface) were observed by energy dispersive X-ray spectroscopy in conjunction with Scanning electron microscopy (SEM) and by X-ray photoelectron spectroscopy.…”
Section: Bonding Behaviormentioning
confidence: 99%
“…Such acidic functional monomers are known to be suitable for base metal alloys [ [14] , [15] , [16] ]. Furthermore, surface oxidation was shown to be the main contributor toward the improved adhesive bonding of a Ag–Pd–Cu–Au alloy [ 13 ]. However, such mechanochemical changes in the surfaces of the silver-based dental alloys caused by alumina air-abrasion and the influence of these changes on the adhesive bond characteristics are still not fully understood.…”
Section: Bonding Behaviormentioning
confidence: 99%